(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The case law of the Federal Supreme Court (STF) is firm in the sense that the reduction in the calculation basis of the Tax on the Circulation of Goods and Services (ICMS) corresponds to a partial exemption, allowing the tax credit to be reversed in proportion to the transactions carried out. The state treasuries argued that the fuel alcohol subsidy, known as the "alcohol price standardization freight" (FUPA), was a kind of partial exemption because it reduced the ICMS tax base. The STF accepted this thesis in a recent judgment (RE-AgR 929.515). It turns out that, in this case, it is necessary to invoke the hermeneutic technique of distinguishing to demonstrate that the jurisprudential precedents that underpinned this judgment are inapplicable. In fact, there are precedents from the STF itself1 to the effect that the tax benefit of reducing the tax base is equivalent to a partial exemption and, therefore, the proportional reversal of the ICMS credit is possible. The case of RE-AgR 929.515, however, does not fall within these judgments. The constitutional dispute is therefore whether or not FUPA credits constitute a partial exemption resulting from a reduction in the tax base or a pure non-taxation. If they do not constitute a tax benefit, then the requirement to reverse the credits in honor of the constitutional rule of non-cumulative taxation is undue.